Inventory of Radio Programs on Environmental Educommunication. - da Silva, Claudionor Renato (2008)
Educommunication is a knowledge area which acts in the interface of education and communication and has as its focus the critical and reflexive formation of the subjects. In this sense, the means of mass communication have become action instruments, assuming an important role, among many others, in the discussions involving environmental themes. This research has the aim of elaborating a preliminary inventory of the existing radio programs in Brazil which treat specifically of environmental education and which are structured on the educommunication assumptions and concepts.The adopted methodology was based on documental analysis, by researching the radio programs in the internet and dissertations and theses produced in the last five years, available at CAPES Bank of theses, emphasizing the following points: name, localization, nature/links (governmental, business, college, etc.) and aims. The results show a non significant amount of radio programs of this type if compared to other types of programs. However, among the mapped programs, it was possible to observe that they have overlapped the mere informative phase and may be considered as instruments of critical , reflexive formation. So, this research has pointed new investigation possibilities relating to the mapping of the universe of educommunication programs and projects, via radio, in environmental education, as well as the necessity of investigation of the efficacy of these programs concerning habit change and social transformation in the places where they are broadcast.